#### Answer

$q = -9$

#### Work Step by Step

$4 = q + 13$
In order to solve this algebraic equation, we will need to isolate the variable $q$ on the right hand side by eliminating the constants from the right hand side. We therefore subtract $13$ from both sides of the equation as shown below:
$4 -13 = q + 13 -13$
Simplify to get:
$-9 = q$
Rearranging it, we have:
$q = -9$
This means that the equation has a possible solution at $q = -9$
Testing:
To test the truth of the statement, we replace for the variable $q$ in the original equation with $-9$ as shown below:
$4 = q + 13$
$4 = -9 + 13$
Simplify to get:
$4 = 4$
This is a proof that the statement $q = -9$ is true.